Media Poster Pada Materi Pencemaran Lingkungan dan Pengaruhnya Terhadap Hasil Belajar Peserta Didik - Jumadin, Jumadin; Muh. Rapi; Muhammad Khalifah Mustami; Syarbini, Nuzul (Al-AHYA: Jurnal Pendidikan Biologi, 2023)
Poster media is an information medium that gives an interesting impression and can make the material easy to understand, increasing interest in learning. This study aims to determine the influence of the use of poster media on environmental pollution material on the learning outcomes of grade VII MTs students' Aisyiyah Sungguminasa Gowa. This study used the quasi-experimental method with a non-equivalent control group design. This study took a sample of 40 learners that were selected with a purposive sampling technique and divided into two groups: the experimental group and the control group. The test instrument used test-learning outcomes, observation sheets (observations), and documentation. Descriptive statistics and inferential analysis were used to analyze the collected data, including a prerequisite test and an independent sample t-test. The results showed that the average value of learning outcomes of students who used poster media (experiment) was 90.25, which was categorized as very good, while the average value of learning outcomes of students who did not use poster media (control) was 62.50, which was in the good category but had not yet reached minimum criteria completion, or KKM. The results of inferential data analysis showed that the significance obtained was t count 0.000<0.05, which means the results showed that the use of poster media significantly affected the learning outcomes of students compared to those who did not use poster media.